Effect of the doping of PC61BM electron transport layer with carbon nanodots on the performance of inverted planar MAPbI3 perovskite solar cells. (1st September 2019) - Subair, Riyas; Di Girolamo, Diego; Bodik, Michal; Nadazdy, Vojtech; Li, Bo; Nadazdy, Peter; Markovic, Zoran; Benkovicova, Monika; Chlpik, Juraj; Kotlar, Mario; Halahovets, Yuriy; Siffalovic, Peter; et al.
Highlights: Carbon nanodots in PC61 BM layer increase efficiency of perovskite solar cell by 12%. Carbon nanodots in PC61 BM strongly slow down deterioration of solar cell performance. Carbon nanodots generate extra free-charge carriers in PC61 BM on cell illumination. Carbon nanodots increase three times conductivity of PC61 BM layer. Abstract: The doping effect of carbon nanodots (CNDs) in the PC61 BM electron-transport layer on the performance of inverted planar MAPbI3 perovskite solar cells (PSCs) having two different kinds of the hole-transport layer, namely organic PEDOT:PSS and inorganic NiOx, was investigated. The CH3 NH3 PbI3 perovskite layer was deposited in air at 35% humidity. An average 11% and 12% enhancement of the power conversion efficiency ( PCE ) was achieved for 1 wt% CNDs doping in the PSCs with PEDOT:PSS and NiOx, respectively. This improvement is attributed to high electron density of CNDs resulting in a triple increase of the electrical conductivity of the PC61 BM layer and passivation of the perovskite/PC61 BM interface that is reflected by an increase of the open-circuit voltage. In line with this, parallel resistance and fill factor of the PSCs are also improved. Moreover, the energy-resolved electrochemical impedance spectroscopy revealed additional free-charge carriers in the PC61 BM layer generated under illumination that were detected via the polaron states formation in the band gap with positive effect on the short-circuit current. All these factors contribute to the PCE improvement. Stability tests of the PSC with PEDOT:PSS under a continuous 24 hour 1.5 AM illumination showed a five times smaller final PCE decrease for the 1 wt% CNDs doping of the PC61 BM layer comparing to the undoped counterpart. The passivation effect of CNDs, namely electron filling the traps formed by the photo-dimerization and photo-oxidation of PC61 BM molecules, is responsible for this remarkable improvement of the short-term stability.